Juridical Construction for Compensation Claims of Domestic Violence in Divorce Cases (Perspective on The Authority of Religious Court) - muhammad natsir asnawi; Fakhir Tashin Baaj (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
The domestic violence-grounded divorce lawsuit in Religious Court has never been followed by a claim for compensation despite the wife suffering losses. In fact, the Religious Court has jurisdiction on property disputes or other civil disputes among Muslims. The reason for the fact was the intersection authority to proceed with a claim of compensation due to domestic violence between the General Court and Religious Court. Consequently, we have yet to reach an optimum legal protection for the wife due to the claim for compensation mechanism still considered under the authority of the General Court. The research is normative research and uses a statutory approach. The problems studied: 1. What is the point of intersection of authority to proceed in cases of civil tort between Religious Court and General Court?; 2. What is the legal construction of combining divorce cases with claims for compensation for domestic violence? The results of the study indicate that the provisions of Article 50 of Law No. 3 of 2006 provide a legal basis for the Religious Court to proceed with a claim for compensation in its particular case. Claims for compensation in a divorce case are constructed as additional claims for unlawful acts in accordance with the principles of speedy administration justice.